Zadania rodziny w świetle przesłania społecznego biskupów katowickich podczas pielgrzymek stanowych w Piekarach Śląskich (1966–2016) - Zoremba, Monika (Studia Pastoralne, 2020)
The family is of enormous value and persons called to form it face numerous tasks. Although the functions and tasks of the family remain the same, certain spheres have been modified, since the family has to deal with new challenges and obstacles. A manifestation of care for the family in Upper Silesia are, inter alia, special messages of bishops of Katowice delivered during annual social class pilgrimages of men and women to Piekary Śląskie. During each pilgrimage, the bishops of Katowice (Herbert Bednorz, Damian Zimoń and Wiktor Skworc) preached on the topic of family. They recognized the value of the family and the scope of the tasks it faces. They talked about various forms of support and appropriate attitudes of a mature Christian. Most of all they emphasised the importance of the sacramental marriage and the fact that marriage is a special gift. They recognised the effort of parents to educate children and adolescents, transfer faith, and shape appropriate Christian attitudes. They were not afraid to touch upon difficult and uncomfortable issues such as the value of human life that should be protected, and protecting the Christian character of Sunday.